Assessment of Alternative Methods of Preparing Internal Combustion Engine Cylinder Bore Surfaces for Frictional Improvement - K., Kadirgama; D., Ramasamy; Kong, Chung Hwa (Springer Berlin Heidelberg, 2017)
A smooth polished surface has a great potential to lead to low friction and wear in internal combustion engines (ICE). Alternative methods to create a smooth dimpled surface on a hypereutectic aluminium (aluminium die cast) ADC12 substrate for frictional improvements are evaluated in this study using an oscillating wear tester (OWT). It was found that the samples embossed with #480 grit sandpaper and sandblasted with #240 sieve sand samples had the more desired properties with a reduced coefficient of friction (μ) of 23% at low sliding speeds before hydrodynamic lubrication mode and 6.9% in the fully hydrodynamic lubrication region. Although samples cast with added graphite powder had much lower friction, it had insufficient oil retention volume and resistance against catastrophic wear.